E-Health Literacy and Cyberchondria Severity among Adolescent High School Students: A Cross-Sectional Study - Çavmak, Seyda; Bilgin, Adem (Makara Journal of Health Research, 2026)
Background: Amid rapid digitalization and the growing use of artificial intelligence-based search engines, adolescents increasingly seek health information online. This study examined the relationship between high school students' e-health literacy and their cyberchondria tendencies. Methods: This quantitative, cross-sectional study included 683 students from public high schools in Mersin, Türkiye. Data were collected using a Demographic Information Form, the e-Health Literacy Scale (eHEALS), and the Cyberchondria Severity Scale Short Form (CSS-12). Descriptive statistics, comparative tests, and Pearson correlation were applied (p < 0.05). Results: Students' e-health literacy and cyberchondria severity were moderate. Significant positive correlations emerged between e-health literacy and all cyberchondria subdimensions (distress, necessity, reassurance, excessiveness). Internet use duration and purpose were associated with cyberchondria; students who had searched for health information within the past week showed significantly higher literacy scores. No significant differences were found by gender or grade level. Conclusion: Higher e-health literacy was associated with more frequent online health searching and greater cyberchondria tendencies, suggesting literacy alone may not reduce this risk. Educational programs should incorporate critical appraisal of online information, misinformation management, and coping strategies for digital health-related anxiety.